Control interno y la ejecución presupuestal de la Municipalidad Distrital de San Juan 2025 - Freitas Villavicencio, Ariana Alexandra (2025)
The purpose of this research was to determine the extent to which internal control is related to budget execution in the District Municipality of San Juan 2025. The study was a basic, quantitative, correlational and non-experimental cross-sectional design. The sample was taken from the total population of 45 workers. In the results, in the internal control variable, 15.5% responded that it was low and 48.9% that it was high. On the budget execution variable, 11.1% responded that it was low and 46.7% that it was high. Likewise, the chi-square test yielded a significance value of 0.000<0.05, which indicates that internal control is significantly related to budget execution in the District Municipality of San Juan 2025.